The Effect of Augmented Reality (AR) Based Multimedia ATLAS: Volcanic Series Volcanism Material on Learning Outcomes of Students of SMAN 2 Blitar - Dianti Lintang Penatas; Brigita Ajeng Andya Hariyana (Future Space: Studies in Geo-Education, 2024)
The presence of Augmented Reality (AR) technology in education supports multimedia advances in learning, one of which is ATLAS: Volcanic Series. The use of multimedia in learning can facilitate the understanding of the material by students, so that good learning outcomes are achieved. The purpose of this research is to know the effect of Augmented Reality (AR) based multimedia ATLAS: Volcanic Series volcanism material on student learning outcomes of SMAN 2 Blitar. Quasi experimental is the type of this research and post-test only group design. As the method, the subjects in this study were students of class X (IPS 3 & IPS 4) SMAN 2 Blitar. Collecting data using quantitative methods through post-test results. The t-test technique (Independent Sample T-test) was carried out for data analysis in order to determine the effect of Augmented Reality (AR) based multimedia ATLAS: Volcanic Series on volcanism material on students' scores or learning outcomes in geography lessons. The results of this 2-week study show that multimedia based on Augmented Reality (AR) ATLAS: Volcanic Series volcanism material has a significant effect on learning outcomes at SMAN 2 Blitar.